Multimodal therapeutic approach and interdisciplinary challenge for the treatment of unresectable head and neck squamous cell carcinoma in six cats: a pilot study. (23rd March 2012) - Marconato, L.; Buchholz, J.; Keller, M.; Bettini, G.; Valenti, P.; Kaser‐Hotz, B.
Abstract Feline head and neck squamous cell carcinoma (SCC) is a loco‐regional disease harbouring a poor prognosis. The complex anatomic location precludes aggressive surgical resection and tumours recur within weeks to few months. Response to chemotherapy and local control after radiation therapy has been disappointing. In this study, a multimodal approach including medical treatment (thalidomide, piroxicam and bleomycin), radiation therapy (accelerated, hypofractionated protocol) and surgery was attempted in six cats. Treatment was well tolerated. Three cats with sublingual SCC were alive and in complete remission at data analysis closure after 759, 458 and 362 days. One cat with laryngeal SCC died of renal lymphoma after 51 days and the other with maxillary SCC died of a primary lung tumour 82 days after diagnosis. In both cats, the SCC was in complete remission. Only one cat developed metastases after 144 days. These encouraging preliminary results merit further evaluation in future trials.